1986
DOI: 10.1083/jcb.102.6.2088
|View full text |Cite
|
Sign up to set email alerts
|

Brain spectrin(240/235) and brain spectrin(240/235E): two distinct spectrin subtypes with different locations within mammalian neural cells.

Abstract: Abstract. Adult mouse brain contains at least two distinct spectrin subtypes, both consisting of 240-kD and 235-kD subunits. Brain spectrin(240/235) is found in neuronal axons, but not dendrites, when immunohistochemistry is performed with antibody raised against brain spectrin isolated from enriched synaptic/axonal membranes. A second spectrin subtype, brain spectrin(240/235E), is exclusively recognized by red blood cell spectrin antibody. Brain spectrin(240/235E) is confined to neuronal cell bodies and dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
175
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(184 citation statements)
references
References 40 publications
9
175
0
Order By: Relevance
“…ELF is expressed in cell bodies as well as dendrites and initial axon segments, and in this sense is unique in its expression pattern from spectrin G and brain spectrin (Goodman et al, 1995). Spectrin G is present in axons and, to a lesser extent, in neuronal cell bodies but not in dendrites (Riederer et al, 1986), while ELF is expressed in both cell types. Brain spectrin (bR), an alternatively spliced form of erythrocyte spectrin, is localized to the perikaryon, dendrites (like ELF/bG), and also glial precursor cells.…”
Section: Tgf-b and Elf (A B-spectrin)mentioning
confidence: 96%
See 1 more Smart Citation
“…ELF is expressed in cell bodies as well as dendrites and initial axon segments, and in this sense is unique in its expression pattern from spectrin G and brain spectrin (Goodman et al, 1995). Spectrin G is present in axons and, to a lesser extent, in neuronal cell bodies but not in dendrites (Riederer et al, 1986), while ELF is expressed in both cell types. Brain spectrin (bR), an alternatively spliced form of erythrocyte spectrin, is localized to the perikaryon, dendrites (like ELF/bG), and also glial precursor cells.…”
Section: Tgf-b and Elf (A B-spectrin)mentioning
confidence: 96%
“…Two genes for a-spectrin (Riederer et al, 1986;Goodman et al, 1995;Ziemnicka-Kotula et al, 1998) and five for b-spectrin have been identified to date in both mice and humans, each of which is alternatively spliced to produce multiple spectrin isoforms (Bennett et al, 1982;Birkenmeier et al, 1988;Gallagher and Forget, 1993;Goodman et al, 1995). A novel bG-spectrin lacks the C-terminal pleckstrin homology (PH) domain that is characterized by elf 1, 2, 3, and 4 (Mishra et al, 1998(Mishra et al, , 1999Hayes et al, 2000).…”
Section: Tgf-b and Elf (A B-spectrin)mentioning
confidence: 99%
“…The direct visualization of ankyrin [Davis and Bennett, 1984b], calmodulin [Tsukita et al, 19831, and antigenic sites [Glenney et al, 1983al on mammalian brain spectrin and the mapping of human brain spectrin functional domains [Harris and Morrow, 1988b;Harris et al, 19881 indicate that these tetramers are arranged in an erythroid-like head-to-head manner. Given the similar composition and morphology of other nonerythroid spectrins, it is likely that all spectrin tetramers are arranged in a similar Bennett [ 19851;3, Bloch and Morrow [1989]; 4, Branton et al [1981]; 5, Byers et al [ 19871;6 , Coleman et al [1989]; 7, Dubreuil et al [1987]; 8, Fishkind et al [1987]; 9, Giebelhaus et al 119871;10, Glenney and Glenney [1983a]; 11, ; 12, Glenney et al [1982b]; 13, ; 14, Goodman and Zagon [1986]; 15, Kuramochi et al [1986]; 16, Lazarides and Nelson [1985]; 17, Marchesi [1985]; 18, ; 19, Pearl et al [1984];20, Pollard 119841;21, Shatten et al [1986]; 22, Shile et al [1985]; 23, Repasky et al [1982]; 24, Riederer et al [1986].…”
Section: Spectrin Self-associationsmentioning
confidence: 99%
“…2,3 The most common and well studied spectrin isoforms are erythroid aIand bI-spectrin, and nonerythroid aII-and bII-spectrin. 1 It is generally accepted that aI-, aII-, bI-, and bII-spectrin are all expressed within neurons, [4][5][6][7][8] with aI-and bI-spectrin found in neuronal cell bodies, dendrites, and postsynaptic terminals of neurons, 9 whereas aII-and bII-spectrin are found in the axon and presynaptic termini. 10 The major functions of spectrin are to maintain cell shape and membrane integrity, with the functional form of spectrin being tetrameric.…”
Section: Introductionmentioning
confidence: 99%